The Relationship Between Fast Food Eating Habits And Hypertension Incidence In Young Adult Women In The Working Area Of The Pasar Ikan Community Health Centre In Bengkulu City In 2025 - Hanila, Rese; Pebriani , Emi; Marlianto, Nuche (Jurnal Multidisiplin, 2025)
The World Health Organisation (WHO) estimates that approximately 972 million people, or 26.4% of the global population, suffer from hypertension, and this figure is projected to rise to 60%, affecting 1.56 billion people by 2025. Of the 972 million people with hypertension, 333 million are in developed countries, and the remaining 639 million are in developing countries, including Indonesia. This study aims to examine the relationship between fast food consumption habits and the incidence of hypertension among young adult women in the Bengkulu City Pasar Ikan Community Health Centre Working Area in 2025. The research method used is analytical observational research with a cross-sectional approach. The sampling technique used is purposive sampling with a sample size of 69 young adult women. The results of the univariate analysis showed that most of the respondents (65.2%) often ate fast food, and almost half of the respondents (42%) had hypertension. The results of the bivariate analysis showed a relationship between fast food consumption habits and the incidence of hypertension in young adult women (p=0.000). There is a relationship between the habit of eating fast food and the incidence of hypertension in young adult women in the working area of the Pasar Ikan Community Health Centre in Bengkulu City in 2024. The researchers suggest that respondents reduce their consumption of unhealthy fast food, such as foods containing fat and foods high in sodium or salt, which can increase the incidence of hypertension.